Linguocultural Analysis of Key Concepts in Abai Kunanbaev’s “Words of Edification” - M, Khavaidarova M.; D, Abisheva S.; Zhanna, Tolysbayeva; Gulnara, Abdikerimova; Aliya, Ongarbaeva; G, Atebayeva (Journal of Cultural Analysis and Social Change, 2026)
The article is devoted to the linguacultural analysis of key concepts in the work "Words of Edification" by Abai Kunanbayev - a fundamental text of the Kazakh spiritual culture. The study is aimed at identifying concepts that form the core of the Kazakh linguistic picture of the world, such as akyl (reason), iman (faith), adam (man), kairat (will), gylym (knowledge), namys (dignity), kanagat (moderation) and others. These concepts are considered not only as lexical units, but also as carriers of mental, ethical and cultural meanings.The methodological basis of the study includes conceptual, contextual, comparative and semiotic analysis, as well as the principles of cognitive linguistics and the lexical-semantic approach. Particular attention is paid to the issue of interpreting concepts when translating from Kazakh into Russian, which allows us to identify losses, distortions or rethinking of meanings. The analyzed translations (A. Semenova, L. Slovokhotova, M. Auezova) showed that such concepts as namys, iman and kanagat, when moving to another linguistic and cultural code, lose part of their pragmatic and axiological load.The author emphasizes that the "Words of Edification" represent a kind of "linguocultural code" of the Kazakh nation. They record a holistic system of values, reflecting the national worldview, norms of behavior, ethnic identity and educational guidelines.